FUNCTIONAL FOODS INNOVATION: HIGH CALORIE LIQUID FORMULATIONS AND ITS ACCEPTABILITY AMONG IIUM KUANTAN STUDENTS - Hazali, *Norazlanshah; Osman, Saifullah; Mohd Fadzlan, Fazlyla Nadya (Malaysian Journal of Science, 2013)
Nowadays, with the advancement of science and nutritional breakthrough, there are lots of methods can be applied to optimise energy and nutritional requirement. One of the approaches is through utilisation and modification of functional foods available. Some of these functional foods are high in calorie and nutrient dense. Therefore, the aim of the research was to develop simple formulations of healthy high calorie beverages derived from functional foods. Four formulations with different main ingredients were evaluated. The formulations were subjected to macronutrients analysis and sensory evaluation for measurement of the acceptability. The main sensory properties such as appearance, aroma, consistency, colour, after taste, and overall acceptance were evaluated using a nine point Hedonic scale. Nutritionist Pro™ software was used to compare the nutrient content. Based on the analysis performed, Enercal Plus® which was the control formulation shown the densest calorie for one serving (360 kcal/serving) followed by F2, F3, and F1 formulations. The results of hedonic rating proved that all formulations showed fair acceptability with the highest percentage and hedonic score goes to control formulation of Enercal Plus® followed by F3, F2, and F1 formulations. Their mean score ranged between 5- 6.6 in terms of general acceptability. From this research, it showed the development of high calorie beverage is possible through modification of functional foods. Keywords: Functional foods, formulation, high calorie, sensory evaluation, hedonic score. Abstrak Dengan kemajuan dalam bidang sains dan kejayaan dalam bidang pemakanan pada masa kini, terdapat pelbagai kaedah yang boleh digunakan untuk mengoptimumkan keperluan tenaga dan pemakanan. Salah satu pendekatannya adalah dengan pengunaan dan pengubahsuian makanan berfungsi yang tersedia. Sesetengah makanan berfungsi ini tinggi kalori dan padat dengan nutrient. Maka, tujuan kajian ini adalah untuk menghasilkan formulasi mudah minuman tinggi kalori yang dihasilkan daripada makanan berfungsi. Empat formulasi dengan bahan utama yang berbeza dinilai. Formulasi-formulasi ini menjalani analisis makronutrien dan penilaian sensori untuk menentukan penerimaannya. Ciri-ciri sensori yang utama seperti rupabentuk, aroma, konsistensi, warna, rasa kesan dan penerimaan keseluruhan dinilai menggunakan skala Hedonik 9 titik. Perisian Nutritionist Pro™ digunakan untuk membandingkan kandungan nutrient. Berdasarkan analisis yang dijalankan, Enercal Plus® yang merupakan formulasi kawalan mempunyai kandungan kalori paling padat untuk satu hidangan (360 kcal/hidangan) diikuti dengan formulasi F2, F3 dan F1. Keputusan penilaian hedonik menunjukkan kesemua formulasi mecapai tahap penerimaan yang baik dengan peratusan tertinggi dicapai oleh Enercal Plus® diikuti dengan F3, F2 dan F1. Skor min kesemua formulasi adalah antara 5-6.6 berdasarkan penerimaan keseluruhan. Kajian ini menunjukkan pembangunan minuman berkalori tinggi melalui pengubahsuian makanan berfungsi mampu tercapai. (Keywords: Fuctional food, high calorie, IIUM, Nutritionist Pro™, Enercal Plus®)